Financial Theories of Yield Curve - Asror Komilov (Genius Journals, 2022)
This article talks about financial theories. Several yield curve theories have been explained including: Expectations theory, Segmented Marketes theory, Liquidity Premium and Preferred Behaviour theories. The main fundamental differences of yield curve theories have been identified.
Keywords: Financial theories; finance; Expectations theory